The use of multivariate statistical analysis in lipid biomarker studies - Masni Mohd Ali,; Stephen M. Mudge, (Universiti Kebangsaan Malaysia, 2005)
Fatty acids, fatty alcohols and sterols have been determined for a sediment core taken from the Conwy Estuary, United Kingdom. These biomarkers were used to identify temporal variations in organic matter sources within the estuary. Principal Component Analysis (PCA) was used to distinguish the dominant source signatures. PCA for individual chemical group successfully classified fatty acids, fatty alcohols and sterols as either principally terrestrial or principally marine/bacterial. However, PCA was not able to separate the marine and bacterial derived compounds. The same observation was shown when PCA was carried out with the combination of fatty acids, fatty alcohols and sterols.